Strategi Media Relations Dalam Pembentukan Brand Image Universitas Muhammadiyah Jakarta - Sheren Regita Cahyani; Suhaimah .; Salsabilla Narissa Devyanti; Sadiyah El Adawiyah (CV. ITTC INDONESIA, 2026)
This study analyzes the media relations strategy of Muhammadiyah University Jakarta (UMJ) in shaping its brand image amid fierce competition between private and public universities. Using a descriptive qualitative approach, primary data was obtained through in-depth interviews with the Head of UMJ Public Relations (Sofia Hasna), journalists, and public respondents, supported by secondary data from institutional documents and media reports.Data analysis followed Miles and Huberman's interactive model with triangulation of sources for validity. The results show that UMJ's media relations strategy is coordinated by the University Secretariat Office through the synergy of public relations, multimedia, and protocol, with significant strengthening since 2024/2025. The conventional-digital hybrid approach includes information transparency, strict SEO-based coverage SOPs, situational spokespersons, and personal relationships with top-tier media such as Kompas and Detik.com. This strategy shapes UMJ's brand image as an